2018
DOI: 10.1115/1.4041230
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Motion of Bubbles in a Centrifugal Pump Impeller

Abstract: Centrifugal pumps operate below their nominal capacity when handling gas–liquid flows. This problem is sensitive to many variables, such as the impeller speed and the liquid flow rate. Several works evaluate the effect of operating conditions in the pump performance, but few bring information about the associated gas–liquid flow dynamics. Studying the gas phase behavior, however, can help understanding why the pump performance is degraded depending on the operating condition. In this context, this paper presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Sato et al [10] performed visualizations for various impeller blade angles. More recently, Stel et al [11] investigated the bubbles using a high speed camera to track the bubble motion, allowing for an understanding of coalescence effects. Mansour et al [12] performed an experimental analysis on both an open and closed 2D impeller pump aiming to more precisely define pump surge and break-down locations.…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al [10] performed visualizations for various impeller blade angles. More recently, Stel et al [11] investigated the bubbles using a high speed camera to track the bubble motion, allowing for an understanding of coalescence effects. Mansour et al [12] performed an experimental analysis on both an open and closed 2D impeller pump aiming to more precisely define pump surge and break-down locations.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of local void fraction in two phase flows recently obtained by Schäfer et al [11], using the X-ray tomography technique, also detected a thin gas film on the pressure side for the first time. In addition, Stel [12] proposed a force analysis in order to track single bubble trajectories, based on a Lagrangian approach, including bubble size effects. This analysis, however, does not take into account bubble interactions.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computer technology, numerical simulations based on computational fluid dynamics (CFD) are being widely used in engineering optimization design and performance prediction [28]. Stel et al [29] indicated that the displacement of bubbles in an impeller is hindered by the increase in the bubble diameter and impeller speed but facilitated by increase in the liquid flow rate. Furthermore, one can understand the pattern of the bubble trajectories by performing a force analysis.…”
Section: Introductionmentioning
confidence: 99%